Investigating the influence of intermittent and continuous mechanical loading on skin through non-invasive sampling of IL-1α. Issue 1 (February 2019) - Soetens, J.F.J.; Worsley, P.R.; Bader, D.L.; Oomens, C.W.J.
Abstract: Pressure ulcers (PUs) are a major burden to both patients, carers and the healthcare system. It is therefore important to identify patients at risk and detect pressure ulcers at an early stage of their development. The pro-inflammatory cytokine IL-1 α is a promising indicator of tissue damage. The aim of this study was to compare the temporal skin response, by means of IL-1 α expression, to different loading regimens and to investigate the presence of individual variability. The sacrum of eleven healthy volunteers was subjected to two different loading protocols. After a baseline measurement, the left and right side of the sacrum were subjected to continuous and intermittent loading regimen, respectively, at a pressure of 100 mmHg. Data was collected every 20 min, allowing for a total experimental time of 140 min. Sebum, collected at ambient conditions using Sebutape, was analyzed for the pro-inflammatory cytokine IL-1 α . Most robust results were obtained using a baseline normalization approach on individual data. The IL-1 α level significantly changed upon load application and removal ( p < 0.05 ) for both loading regimens. Highest IL-1 α ratio increase, 3.7-fold, was observed for 1 h continuous loading. During the refractory periods for both loading regimen the IL-1 α levels were still found to be up-regulated compared to baseline ( p < 0.05 ). The IL-1 α level increased significantly for the two initial loading periods ( p < 0.05 ), but stabilized during the final loading period for both loading regimens. Large individual variability in IL-1 α ratio was observed in the responses, with median values of 1.91 (range 1.49–3.08), and 2.52 (range 1.96–4.29), for intermittent and continuous loading, respectively, although the differences were not statistically significant. Cluster analysis revealed the presence of two distinct sub-populations, with either a low or high response to the applied loading regimen. The measurement after the first loading period proved to be representative for the subsequent measurements on each site. This study revealed that trends in normalized IL-1 α provided an early indicator for tissue status following periods of mechanical loading and refractory unloaded conditions. Additionally, the observed individual variability in the response potentially identifies patients at risk of developing PUs. Highlights: Normalized IL-1α levels reflect the applied temporal loading profile. No differences were found between the intermittent and continuous loading responses. Large individual variability was observed in the participant-specific responses. This variability potentially indicates the individual susceptibility to PU development. The individual responses were significantly indicated after the first loading period.